Pharmacological Properties, Therapeutic Potential and Molecular Mechanisms of JWH133, a CB2 Receptor-Selective Agonist - Hashiesh, Hebaallah Mamdouh; Sharma, Charu; Goyal, Sameer N.; Jha, Niraj Kumar; Ojha, Shreesh (Frontiers in Pharmacology, 2021)
The endocannabinoid system has attracted attention as a pharmacological target for several pathological conditions. Cannabinoid (CB2)-selective agonists have been the focus of pharmacological studies because modulation of the CB2 receptor (CB2R) can be useful in the treatment of pain, inflammation, arthritis, addiction, and cancer and provide neuroprotection, among other possible therapeutic applications while circumventing CNS-related adverse effects. An increasing number of evidence from different independent preclinical studies has suggested new perspectives on the involvement of CB2 signaling in inflammation, diabetes, cardiovascular disease, cancer, and atherosclerosis. JWH133 is a synthetic agonist with high CB2R selectivity and antioxidant, anti-inflammatory, anticancer, cardioprotective, hepatoprotective, gastroprotective, nephroprotective, and immunomodulatory activities. Recent studies indicate that it also possesses neuroprotective effects. Evidence also suggests that JWH133 protects against hepatic injury, renal injury, cardiotoxicity, fibrosis, rheumatoid arthritis, and cancer as well as against oxidative damage and inflammation, inhibits fibrosis and apoptosis, and acts as an immunosuppressant. This review provides a comprehensive overview of the polypharmacological properties and therapeutic potential of JWH133 and its molecular mechanism and signaling pathways under various pathological conditions. This review proposes the possible application of JWH133 as a promising therapeutic agent; however, further clinical trials in humans are warranted to affirm these activities.